Correlated iron 60, nickel 62, and zirconium 96 in refractory inclusions and the origin of the solar system - Quitte, G; Halliday, A; Meyer, B; Markowski, A; Latkoczy, C; Guenther, D (2007)
We report precise nickel isotopic compositions, measured with high-resolution MC-ICPMS, for calcium-aluminum-rich inclusions (CAIs) considered to be the earliest objects formed in the solar system. The CAIs display correlated anomalies of 60Ni and 62Ni, possibly coupled with effects on 96Zr. This is not predicted from stellar production models unless the 60Ni results from the decay of 60Fe. The effects show the signature of neutron-burst nucleosynthesis in a massive star. Such a neutron burst is plausibly responsible for the abundance of many of the short-lived radioactivities present in the early solar system; therefore, at least some of the nucleosynthetic heterogeneity previously reported from CAIs, leached carbonaceous chondrites, and presolar grains is likely to have been generated by dust injection from a supernova at a time close to the beginning of the solar system, which is consistent with a trigger for solar nebula collapse, or generated directly by dust injection into the protoplanetary disk. © 2007. The American Astronomical Society. All rights reserved.